KEANEKARAGAMAN JENIS MAKROALGA YANG BERPOTENSI SEBAGAI BAHAN OBAT DI PERAIRAN PANTAI CIDATU KABUPATEN PANDEGLANG - Haris Shobir; Triastinurmiatiningsih .; Ismanto . (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2019)
Macroalgae have various types of polysaccharides such as alginate, gelatin, and bioactive compounds and contain potential pigments as drugs. Research on the diversity of macroalgae types that are potentially as medicinal substances in the waters of Cidatu Beach Pandeglang has done. Research is done by transek method. Sampling locations are differentiated into three stations. Each station is made of three transect with a distance between 5 m and each transect consisting of five plots 1x1 m with a distance between plots 5 m. The potentially medicinal macroalgae in the waters of Cidatu are 10 species which are 3 species of the Chlorophyceae class (Ulva intestinalis, Ulva reticulata and Chaetomorpha crassa), 4 species of the class Phaeophyceae (Padina australis, Turbinaria decurrens, Sargassum crassifolium, and Sargassum polycystum) and 3 species of the class Rhodophyceae (Gracilaria salicornia, Gracilaria coronopifolia and Gelidium sp). The index of diversity in Cidatu beach is 2.169 which is categorized diversity moderate type.